Movement-Based Programs in U.S. and Canadian Public Libraries: Evidence of Impacts from an Exploratory Survey - Lenstra, Noah (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2017)
Objective – Past research suggests that approximately 20-30% of public libraries in the United States offer movement-based programs, that is programs that encourage, enable, or foster physical activity and physical fitness. Little is currently known about the impacts of these programs, in the U.S. or elsewhere. This study addresses the questions: what impacts do movement-based programs in public libraries have and what variations exist between urban and rural libraries.Methods – The researcher aimed to explore these questions through an exploratory survey of U.S. and Canadian public libraries that have offered movement-based programs. The survey was completed by self-selecting staff from 1,157 public libraries in the U.S. and Canada during spring 2017. Analysis focuses on those portions of the survey that address the impacts of movement-based programs.Results – Results show that throughout North America, public libraries provide movement-based programs for all age groups. The most consistently reported impact of these programs is new library users. Furthermore, on average respondents report that participation in these programs slightly exceeding their expectations. These facts may account for the finding that 95% of respondents report that they intend to continue offering movement-based programs at their libraries.Conclusion – More research using a randomized survey design is needed to better assess this emerging programming area in a more comprehensive manner. Nonetheless, this study provides needed evidence on the impacts of movement-based programs in many North American public libraries. Hopefully this evidence will contribute to more conversations and research on the roles of public libraries in public health and wellness.